Induced Pluripotent Stem Cells and Hormesis - Edward J Calabrese (SAGE Publishing, 2022)
This paper represents the first assessment of agent-induced hormetic dose responses in induced pluripotent stem cells and their derived cells. The hormetic dose responses were induced by a broad range of chemicals, including pharmaceuticals (eg, metformin), dietary supplements/extracts from medicinal plants (eg, curcumin), and endogenous agents (eg, melatonin). The paper assesses the mechanistic foundations of these induced hormetic dose responses, their therapeutic implications and comparison with hormetic responses in multiple adult and embryonic stem cells.